2020
DOI: 10.21037/jtd.2020.03.88
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic syndromes in small cell lung cancer

Abstract: Paraneoplastic syndromes can commonly occur due to lung cancer, especially small cell lung cancer. Frequently paraneoplastic syndromes can precede the diagnosis of the neoplasm or present with limited stage disease. However, these syndromes can also occur at the time of recurrence or metastasis of disease. This review focuses on the epidemiology, pathogenesis, clinical features, and current management of the most common paraneoplastic syndromes encountered in patients with small cell lung cancer.Manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 75 publications
0
36
0
2
Order By: Relevance
“…Numerous paraneoplastic syndromes have been identified in connection with a variety of malignancies. The “classic” cancer type to produce numerous paraneoplastic syndromes is SCLC, which has been commonly associated with Cushing’s syndrome and syndrome of inappropriate anti-diuretic hormone amongst others [ 76 ]. Generally, the pathophysiology of antibody-driven paraneoplastic syndromes is thought to be led by an immune attack against tumor antigens, which then forms antibodies that attack non-tumor cells and organs.…”
Section: Autoantibodies In Cancer-associated Paraneoplastic Syndromesmentioning
confidence: 99%
“…Numerous paraneoplastic syndromes have been identified in connection with a variety of malignancies. The “classic” cancer type to produce numerous paraneoplastic syndromes is SCLC, which has been commonly associated with Cushing’s syndrome and syndrome of inappropriate anti-diuretic hormone amongst others [ 76 ]. Generally, the pathophysiology of antibody-driven paraneoplastic syndromes is thought to be led by an immune attack against tumor antigens, which then forms antibodies that attack non-tumor cells and organs.…”
Section: Autoantibodies In Cancer-associated Paraneoplastic Syndromesmentioning
confidence: 99%
“…A strong correlation with cigarette smoking [8] implies a potentially high tumor mutational burden (TMB) as well as high neoantigen diversity [9]. Furthermore, the established occurrence of auto-immune paraneoplastic manifestations in SCLC, such as Lambert-Eaton myasthenic syndrome, sensory neuropathy, limbic encephalitis, and syndrome of inappropriate secretion of antidiuretic hormone, highlight the strong immunogenic feature of SCLC cells [10,11]. Unfortunately, SCLC initial studies have suggested only modest responses to single-agent immunotherapy, and classical predictive biomarkers of immunotherapy were not found to be of benefit for patients with ES-SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal small cell carcinoma is a rarer entity, accounting for <0.5% of all primary laryngeal cancer diagnoses [ 2 ]. Paraneoplastic syndromes are known complications of small cell malignancies, occurring in 1–7.4% of cases [ 3 ]. The majority of the syndromes are endocrine related with rheumatological and immunological complications known to be less frequently encountered.…”
Section: Introductionmentioning
confidence: 99%